Stable or stagnant? Political economy and governance in the United Kingdom, France, Italy and Germany since 2000 - Edward L. Knudsen (Global Policy, 2023)
At the beginning of the twenty-first century, the large democracies of Western Europe experienced some of the most prosperous and peaceful decades in human history. Specifically, the United Kingdom, France, Italy and Germany experienced high and stable quality of life, democratic accountability and state capacity between 2000 and 2019, according to the 2022 Berggruen Governance Index. While all four of these countries are among the top performers in the Index, substantial problems lurk beneath the surface. Notably, each failed to capitalise on the low interest rate environment in the decade following the global financial crisis of 2007–2009—albeit in different ways and for different reasons in each country. In particular, low investment in infrastructure and key technologies, the persistence of stubborn regional inequalities, and resulting sluggish GDP growth have prevented the `Big Four' in Western Europe from improving further and future-proofing their existing gains.
Keywords: 320